Effect of Sintering Temperature on Bi2-xCuxPb0.3Sr2Ca2Cu3O10+δ Superconductors - Abbas, L K; Abbas, M M; Mahdi, O S (Al-Nahrain Journal of Science, 2012)
High temperature superconductors with a nominal composition Bi2-xCuxPb0.3Sr2Ca2Cu3O10+δ for (0≤x≤0.5) was prepared by solid state reaction method. The effect of sintering temperature and substitute of Cu on Bi2-xCuxPb0.3Sr2Ca2Cu3O10+δ compound has been investigated by X-ray diffraction , resistance measurements and oxygen content to obtain the optimum conditions for the formation and stabilization of the high TC phase (2223- phase).The results showed that the optimum sintering temperature for the composition Bi2-xCuxPb0.3Sr2Ca2Cu3O10+δ is Ts=860˚C for ts=140h.The x-ray diffraction (XRD) analysis showed that all the samples have almost two phases: high-Tc phase (2223- phase) and low-TC phase (2212- phase) in addition to the existing of very low phase in the sample x=0.4. It was found that all the samples having an orthorhombic structure with lattice parameter value (c) increased with increasing of the critical temperature Tc. Substitution of Cu to 0.2, 0.3, 0.4 will increase the transition temperature to TC=127K, 130K, 125K, respectively with increasing oxygen content.